Invasive pulmonary aspergillosis treatment duration in haematology patients in Europe: An EFISG, IDWP‐EBMT, EORTC‐IDG and SEIFEM survey. Issue 5 (4th March 2020) - Lanternier, Fanny; Seidel, Danila; Pagano, Livio; Styczynski, Jan; Mikulska, Malgorzata; Pulcini, Celine; Maertens, Johan; Munoz, Patricia; Garcia‐Vidal, Carol; Rijnders, Bart; Arendrup, Maiken Cavling; Sabino, Raquel; et al.
Summary: Invasive pulmonary aspergillosis (IPA) optimal duration of antifungal treatment is not known. In a joint effort, four international scientific societies/groups performed a survey to capture current practices in European haematology centres regarding management of IPA. We conducted a cross‐sectional internet‐based questionnaire survey in 2017 to assess practices in sixteen European countries concerning IPA management in haematology patients including tools to evaluate treatment response, duration and discontinuation. The following four groups/societies were involved in the project: European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Fungal Infection Study Group (EFISG), Infectious Diseases Working Party‐European Society for Blood and Bone Marrow Transplantation (IDWP‐EBMT), European Organisation for Research and Treatment‐Infectious Disease group (EORTC‐IDG) and Sorveglianza Epidemiologica Infezioni nelle Emopatie (SEIFEM). A total of 112 physicians from 14/16 countries answered the survey. Galactomannan antigen was available in serum and bronchoalveolar lavage in most centres (106/112 [95%] and 97/112 [87%], respectively), quantitative Aspergillus PCR in 27/112 (24%) centres, β‐D‐glucan in 24/112 (21%) and positron emission tomography in 50/112 (45%). Treatment duration differed between haematological malignancies, with a median duration of 6 weeks [IQR 3‐12] for patients with AML, 11 [4‐12] for patients with allogenic stem cell transplantation and GvHD and 6 [3‐12] for patients with lymphoproliferative disease. Treatment duration significantly differed according to country. Essential IPA biomarkers are not available in all European countries, and treatment duration is highly variable according to country. It will be important to provide guidelines to help with IPA treatment cessation with algorithms according to biomarker availability.